Association between exposure to secondhand smoke and sleep bruxism in children: a randomised control study. Issue 4 (13th January 2012) - Montaldo, Luisa; Montaldo, Paolo; Caredda, Elisabetta; D'Arco, Anna
Abstract : Background: Exposure to secondhand smoke (SHS) is a serious public health threat and represents a preventable cause of morbidity among children. Sleep bruxism is characterised by teeth grinding or clenching movements during sleep and may begin in adulthood as well as in childhood. Objectives: To investigate the association between SHS exposure and sleep bruxism in children. Methods: Sleep bruxism was investigated in 498 children (mean age: 9.2±1.9). Family members were interviewed and asked whether they smoked in the presence of their children. Children were classified according to their exposure to SHS into heavily, moderately, lightly and occasionally exposed. Children with sleep bruxism and exposed to SHS were randomly divided into two groups: children in group 1 were not exposed to SHS for 6 months, whereas children in group 2 were. Results: Thirty-one per cent of the children under investigation suffered from bruxism. Among them, 116 children (76%) were exposed to SHS. Exposed children showed a higher risk of sleep bruxism (p<0.05). After 6 months, sleep bruxism was found in 38% and in 90% of children, in the first and in the second group, respectively, this difference was statistically significant (p<0.05). In group 1, changes were statistically significant in those who were heavily and moderately exposed (p<0.05) but not in those lightly and occasionally exposed (p>0.05). In group 2, changes were not statistically significant (p>0.05). Conclusion: The findings showed that high and moderate exposure to SHS is associated with sleep bruxism in children.